The Effect Of Leadership And Compensation On Work Discipline At Napoly Jaya Building Store Company in Tasikmalaya City - Mufti Kamil Hidayat; Barin Barlian; Arga Sutrisna (Penerbit Jurnal Indonesia, 2022)
This study aims to determine leadership and compensation for the work discipline of the Napoli Jaya building shop company. The method used is descriptive with a quantitative approach. pollution and a sample of 30 employees of the Napoli Jaya building shop based on the saturated sample technique. The analytical tool used is multiple linear regression. The results show that leadership and compensation simultaneously have a significant effect 12,944%. Partially, leadership has no effect 5,107% and compensation has a significant effect 46,922% on work discipline in the Napoli Jaya building shop.